Historicising appropriability: Hybrid Shakespeare and the challenges of history. Issue 1 (July 2019) - Márkus, Zoltán
With the aid of a specific (or idiosyncratic) understanding of the concept of appropriation that suggests that appropriations are reciprocal manoeuvres of hybridisation that negotiate and construct both their subjects and their objects at the same time, this article explores Shakespeare as a cultural hybrid. In closing, it deploys the preceding theoretical considerations to investigate the cultural and temporal aspects of an anecdote about the Hungarian theatre director Arthur Bárdos.